The Role of Emotion Regulation and Core Autism Symptoms in the Experience of Anxiety in Autism - Conner, Caitlin M. (Autism, 2020)
Youth with autism spectrum disorder (ASD) are at elevated risk for impaired emotion regulation (ER) and clinically impairing anxiety. A prior developmental framework posited that impaired ER leads to co-occurring psychiatric conditions such as anxiety, with outcome determined in part by ASD-specific moderating factors. Using measures developed and validated in ASD, this study evaluated: 1) the association between ER and anxiety in a large, community-based sample of youth with ASD and a wide range of intellectual and verbal abilities; and 2) whether greater core ASD symptoms strengthened the association between impaired ER and anxiety. Parents of 1,107 children with a community diagnosis of ASD (881 boys; age 6–17 years) participated in an online survey assessing their child’s ER, anxiety, and ASD symptoms. ER impairment significantly predicted whether participants had elevated levels of anxiety, after controlling for demographic variables and ASD symptoms; however, there was no interaction of ER and ASD symptoms. This study is the first to support the anxiety-ER association with measures developed and validated specifically for ASD, in a large sample with co-occurring ID and minimally verbal youth with ASD.